Fenomena Mahasiswa Menikah Muda Pada Masa Studi Menuju Keluarga Sakinah Mawadah Warahmah Di Universitas Islam Negeri Sumatera Utara Medan - Intan Purnama Sari Siregar, Husnel Anwar, Husna Sari Siregar (Center of Knowledge : Jurnal Pendidikan Dan Pengabdian Masyarakat, 2021)
This study aims to examine and understand the responses of students at the State Islamic University of North Sumatra regarding the existence of young marriages that occur among students. Marriage is one of the most important things to live in a perfect society blessed by Allah SWT and from there to achieve a happy home life that results in a prosperous family. Physical and spiritual wealth is the dream of every family and it is the highest priority in life. Marriage is also regulated in government law, physically and mentally between a man and a woman as husband and wife, with the aim of forming a happy and eternal family based on the teachings of Islam. Marriage is an act or worship that is considered a practice in Islamic teachings. Marriage has the main goal of forming a sakinah family in addition to other goals, namely: satisfaction of sexual needs, self-preservation, and worship. The formation of the Sakinah family is influenced by elements of religious knowledge, education, business, health, and good relationships. Because this is what underlies some students of the State Islamic University of North Sumatra to decide to get married during the study period. This of course can affect the quality of student education because the focus and objectives are divided. Therefore, the author wants to research and find out how the process and causes of students deciding to marry young during the study period.